Diversity of edible plants sold in two traditional markets of Wonosobo District, Indonesia - DITA OKTAVIA; DANAR THOORIQ AZIZ FATHURROHMAN; EUNIKE ISLAMI FAIRUZ SALSABILA; EVIRAHMALIA NABILA AXELANDRA; RATNA WIDYANINGTYAS; JOHAN ISKANDAR; DARLINA MD. NAIM; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Oktavia D, Fathurrohman DTA, Salsabila EIF, Axelandra EN, Widyaningtyas R, Iskandar J, Md, Naim D, Setyawan AD. 2025. Diversity of edible plants sold in two traditional markets of Wonosobo District, Indonesia. Biodiversitas 26: 5334-5351. The existence of food plants at the Wonosobo Traditional Market in Wonosobo District, Central Java, Indonesia, contributes significantly to supporting biodiversity. This study explores the diversity of edible plants in Kertek Market (Pasar Kertek) and Wonosobo Central Market (Pasar Induk Wonosobo), Central Java, Indonesia. These markets, beyond being trading centers, serve as vital spaces for preserving local culture and bolstering local food security. Through observation and interviews with 102 edible plant traders at Kertek Market and Wonosobo Central Market, we identified a total of 106 species and 161 varieties from 49 families were identified, with the main categories including staple foods, substitute food, vegetables, fruits, and seasonings. The Solanaceae, Fabaceae, Poaceae, and Brassicaceae families dominated. The results showed 88.58% similarity of edible plants sold in both markets, with the Wonosobo Central Market showing higher species and local varieties diversity. Most of the crops sold are cultivated and can be grown all year round. The price interval of edible plants sold ranged from IDR 2,000 to IDR 200,000. The distribution system in this traditional market involves a supply chain from farmers and distributors to consumers, which includes suppliers from Wonosobo District 71%and others (29%). Collaboration between local and external suppliers can support the sustainability of traditional markets underscore the importance of traditional markets as biodiversity reservoirs, and inform local food policy for sustainable agri-food systems.